Music in art - Dorot, Ruth (Studia Europaea Gnesnensia, 2019)
In this article I shall describe the various roles and meanings of music in selected works of different artists, styles and periods, from the basic level of imitating and portraying reality to more covert meanings. The choice of works was based on the starting point of the centrality of music or the role of the musical instrument, or both as a key to understanding and interpreting the painting.